Columbine as a type of youth destructivism - A. A. Glukhova; A. A. Iudin; D. A. Shpilev (Russian Journal of Economics and Law)
Objective: to analyze the reasons for senior schoolchildren’s interest to destructive social groups dedicated to challenges, criminal culture, weapons, erotic and sex, dangerous leisure, death and suicide, mass killings and violence, and drugs; to describe the hierarchy of interests and life values of adolescents based on the research results (questionnaire survey of schoolchildren and multidimensional content analysis of VKontakte social network).Methods: general scientific (analysis, system-structural approach to the analysis of the research object, comparative-legal method) and specific scientific methods (questionnaire survey of schoolchildren, N = 589, conducted in April 2021, and multidimensional content analysis of VKontakte social network, 314,708 fragments).Results: the interests of schoolchildren to various groups in social networks were analyzed. The determinants of joining groups are factors such as the degree of trust in relationships with parents, plans for the future, the amount of time spent daily on the Internet, the tendency to hedonism in everyday life. The methods of involving adolescents in the destructive ideology of the Columbine* movement were revealed.Scientific novelty: two groups of users of sites propagating the destructive ideology of Columbine movement were identified: the core (characterized by the abundance of negative moods, these social network users are potentially capable of committing terrorist acts) and the periphery (characterized by an increased general interest in extreme leisure activities). The hierarchy of interests and life values of representatives of the core and the periphery is described; assumptions are made about the ways and reasons for the flow of users from the core to the periphery and back. The study showed that the breeding ground for Columbine and other destructive youth network movements are the adolescents who do not have trust relationships with their parents, are aimed at enjoying life here and now, do not have clear plans for the future, and prefer virtual communication to real one.Practical significance: the materials of the article can be useful to federal and regional authorities in implementing various aspects of youth policy, preventing sociopathic behavior of the youth, ensuring the safety of educational institutions, as well as to scientists researching destructive youth network movements. * Note: The international youth movement "Columbine" ("Schoolshooting") is recognized as a terrorist organization.